Umgang mit Heterogenität im (Fremdsprachen-)Unterricht – Rahmenbedingungen im polnischen Bildungssystem - Jaroszewska, Anna (Neofilolog, 2022)
The aim of the article is to discuss the main Polish educational legislation aimed at promoting diversity and individualization in the the process of schooling. The focus is on dealing with heterogeneity, which has become frequent in Polish schools and kindergartens. This includes various aspects concerning differentiation in children and young people, such as individual developmentental characteristics, gender, socio-cultural environment, special educational needs or giftedness. Heterogeneity requires individualization of the educational process, which also applies to the teaching of foreign languages. This poses a challenge for many teachers, including foreign language teachers. In many respects Polish legislation regulates how to deal with heterogeneity and individualization in the educational context.